Some notes on Lindelöf spaces and P-sets - Levy, Ronnie (Topology Proceedings, 2025)
A few years ago Gary e-mailed me when he found out that we had the same middle name. He suggested that we write a paper together using that name. One subject that I thought might be interesting arose from a paper Alan Dow and I had written ([DL]). Although Gary and I never got around to writing a joint paper on that topic, that exchange got me thinking about P -points and P -sets. (This topic might be appropriate in light of the joke that Peg Daniels relates in her article in this volume.) The notes below are really an excuse to ask some questions which arose in that context.